2021
DOI: 10.1088/1742-6596/1943/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular identification of thermophilic bacteria from litter of mount Galunggung hot spring, Tasikmalaya, Indonesia

Abstract: Thermophilic bacteria from litter deposited at Cipanas hot spring of mount Galunggung, Tasikmalaya, West Java, Indonesia, were isolated using a culture-dependent approach. Medium International Streptomyces Project (ISP) 1 solidified with gellan gum was used as an isolation medium. Isolation plates were incubated at 50°C for three weeks. The physicochemical analysis showed that the hot spring has a neutral pH and temperatures ranging from 50−56°C. A total of 16 bacterial isolates were obtained and purified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In this study, a DAEase was successfully found from bacteria Chelatococcus composti genome. This species of bacteria was firstly found in the left-over of penicillin fermentation [29], but researchers also isolated this species from a spring water in Indonesia [30]. According to the data from Zhang et al, the GC content of the species was 70.9 %, meaning the genome of the species is stable to stay in an environment with a high temperature [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a DAEase was successfully found from bacteria Chelatococcus composti genome. This species of bacteria was firstly found in the left-over of penicillin fermentation [29], but researchers also isolated this species from a spring water in Indonesia [30]. According to the data from Zhang et al, the GC content of the species was 70.9 %, meaning the genome of the species is stable to stay in an environment with a high temperature [29].…”
Section: Discussionmentioning
confidence: 99%
“…The genome of the bacteria is known to has high GC-content up to 70.9 %. In Indonesia, this bacterium was isolated by Ningsih et al from the litter of hot spring in mount Galunggung, Tasikmalaya [30]. This bacterium inhabits the hot spring with temperatures around 50−56°C at the neutral pH.…”
Section: Chelatococcus Compostimentioning
confidence: 99%
“…Bacillus cereus isolated from the Way Panas hot springs, Kalianda, South Lampung, has high amylolytic activity (Mahestri et al 2021). Several other studies have successfully isolated hydrolytic enzymes from thermophilic bacteria (Zilda et al 2012;Yohandini et al 2015;Laras et al 2017;Ifandi and Alwi 2018;Ningsih et al 2020;Lischer 2021;Geraldi et al 2021;Ginting et al 2021). However, it is the first study on bioprospecting thermophilic bacteria for hydrolytic enzyme production from hot springs in South Sulawesi Province.…”
Section: Introductionmentioning
confidence: 99%